Achieving Record High External Quantum Efficiency >86.7% in Solar‐Blind Photoelectrochemical Photodetection. (29th March 2022) - Liu, Xin; Wang, Danhao; Shao, Pengfei; Sun, Haiding; Fang, Shi; Kang, Yang; Liang, Kun; Jia, Hongfeng; Luo, Yuanmin; Xue, Junjun; Wang, Jin; Zhi, Ting; et al.
Abstract: Controlling interfacial and surface carrier dynamics associated with nanostructured semiconductors is the key to achieving outperforming electrical and optical characteristics in photoelectrochemical (PEC) devices. A strategy for surface renovation by loading a co‐catalyst (functional nanoparticles or layers) can unambiguously empower the device with superior surface property. In this work, a PEC‐type solar‐blind photodetector based on wide‐bandgap p‐AlGaN nanowires is reported on which Rh–Cr2 O3 hybrid structures are rationally loaded. Impressively, the external quantum efficiency of the devices is strikingly boosted from 28.8% to 86.7%, while a record‐high responsivity of 178.3 mA W −1 is achieved, exhibiting one of the highest values among PEC photodetectors. Both experimental insights and theoretical modeling reveal that the initial decoration of Rh nanoparticles facilitate the interfacial carrier transfer and separation while optimizing the hydrogen adsorption energy. After subsequent incorporation of the amorphous Cr2 O3 layer, which acts as a molecular sieve, not only can the side reaction over Rh be effectively suppressed, but also the interfacial carrier dynamics and surface chemical reactivity are further boosted, thus contributing to more favorable PEC processes. The work offers a unique synergetic strategy to optimize the surface property of semiconductors for boosting photoresponse performance in aqueous environments for future bio‐ or chemical‐related sensing applications. Abstract : A photoelectrochemical (PEC) solar‐blind photodetector composed of Rh–Cr2 O3 hybrid modified AlGaN nanowires is reported. Both experimental and theoretical insights reveal the synergetic effect of the Rh–Cr2 O3 co‐catalyst on interfacial carrier behaviors and surface chemical reactivity, resulting in remarkably boosted external quantum efficiency from 28.8% to 86.7% and photoresponsivity of 178.3 mA W −1, outperforming all reported aqueous PEC photodetectors.